Achievement of Awareness in a Diabetic Population - Hoque, Mirza Azizul; Islam, Md Sirajul; Khan, Md Abdul Maleque; Aziz, Rehana; Ahasan, HAM Nazmul (Journal of Medicine, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This cross-sectional survey was carried out during the period, October 2005 to December 2005, among 184 randomly chosen diabetic patients in Khulna Diabetic Centre, Khulna, Bangladesh, to evaluate the knowledge of the patients for their control of diabetes mellitus and also to explore the association(s) of their attitude and knowledge regarding diabetic awareness towards educational status and socio-demographic profile. In this study, we found a significant difference, in diabetic awareness to keep correct blood glucose level, in different educational group. But, it did not influence the subjects of different educational group to visit the diabetic clinic. There was no significant difference in the knowledge of correct blood glucose level and in regularity of visit to the diabetic clinic, in rural and urban people. Knowledge of correct blood glucose level varied significantly among male and female patients, although, no significant variation was found among them in visiting to the diabetic clinic. We can conclude that, diabetic education programs can improve self-regulatory behavior and in the long run, can reduce morbidity and mortality. Â  doi:10.3329/jom.v10i3.2008 J Medicine 2009; 10 (Supplement 1): 7-10 Â 